EU Policies in time of coronavirus crisis - Koutsopoulou, Danai-Georgia (HAPSc Policy Briefs Series, 2020)
This paper seeks to uncover the link between the current crisis in the field of migration and asylum policies and the rise of populist polarization in Europe. Provided that normative consistency serves effectiveness, the study reflects on the existing literature, selected legislative acts, and cases. Hence, criticism against the European Union’s heterodetermination and inertia in the political debate is simmering. Populist phenomena all over the spectrum define the supranational policymaking, outweighing voices of inclusion and democracy, if not the very essence of the Union’s value-based system. Contrariwise, liberal democracy shall not only be capable of defending itself and including the alien when the fears come true but also educating its citizens in the democratic realm before enforcement promptitude is practically imperative. All in all, primary and secondary legal norms entail adequate solutions to address the issue institutionally, subject to political determination, and courage.